Peneguhan diagnosis Avian Influenza pada Ayam Petelur yang Mengalami Gejala Penurunan Produksi - Rina Isnawati; Hastari Wuryastuti; R Wasito (Jurnal Sain Veteriner, 2019)
Decreasing egg production is an initial symptom of various diseases that infect commercial layer chickens. Diagnosis of diseases causing the decrease in egg production without high mortality rate is often thought to be caused by other poultry diseases because of the many similarities in manifestation between one disease and another. Avian influenza is a zoonotic infectious disease in poultry that can lead to high economic losses. This study aims to determine the contribution of avian influenza virus (AIV) infection to commercial laying hens showing symptoms of decreased production. The samples were oropharyngeal swabs of commercial laying hens which had symptoms of decreased production at productive age. Laboratory tests were carried out by histopathological examination, detection and identification of AIV with real time reverse transcriptase polymerase chain reaction (qRT-PCR) and isolation with the viral culture technique on fertile chicken eggs. The results showed that there was type A AIV infection based on the qRT-PCR (matrix) test, but the subtypes were not identified (H5, H7, H9). The results of the isolation of the virus in the fertile chicken eggs showed embryonic death in which all embryonic organs show hemorrhages. Allantoic fluid does not agglutinate chicken red blood cells. Histopathological features of the pathognomonic lesions in lungs infected with AIV were severe congestion and hemorrhages. Based on the results of the study, it was concluded that there was a contribution of type A AIV infection. Early diagnosis of AIV could determine more appropriate actions, including control, prevention and eradication.